KONTRIBUSI ILMU KALAM/FILSAFAT ISLAM DALAM PEMBANGUNAN KARAKTER BANGSA - Abdullah, Muhammad Amin (Jurnal Ilmu Ushuluddin, 2014)
The trend of Islamic sciences in the future, especially kalam Science/Islamic philosophy is a religion sciences that haveto interact and dialogue with modern science, the social sciences and humanities. If scientific Kalam and IslamicPhilosophy felt enough with himself (al-muhafadzah âala al-qadim al-shÃ¢lih), refusing to touch and connect with otherscientific (wa al-akhdz bi al- jadid al-ashlah), then there is no future can be expected, morever their contribution to thedevelopment of the nationâs character. This paper describes the themes of what is required to form the new religious(Islamic) worldview that can contribute to the development of the nationâs character. Islamic sciences requires freshijtihad to deal with the contemporary of life, it is not enough just to repeating the experience of the past without lookinghow the development of the present and the future. Past (al-turÃ¢ts) is still needed, but also needed a paradigm shifttowards the present (al-hadÃ¢tsah) in view of the contemporary religious and solve problems, especially those related tothe issue of character development in the format state of the nation (nation-states).